Strategi Manajemen Konflik Kepercayaan Dalam Hubungan Pernikahan (Studi Kasus Long Distance Marriage) - Tamami, Anggita Hardianti; Nafisa, Siti; Triandani, Tania Salsabila; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
The research is aimed at knowing conflict management strategies against trust in a long distance merrige, as well as in keeping marriage commitments alive. The respondents in this study are that couples pursue long - range marriage relationships because of working factors. Research is conducted using a descriptive qualitative approach. The study samples were taken predictably. Data collection through interviews and observations. Data analysis is done with data reduction, presents data, and concludes. Research has shown that each pair with the other has a conflict management strategy, so the issues that arise are solvable. The application of conflict management strategies from each pair has a distinct effect on the success of couples working to maintain commitment and trust between long distance merrige during periods of separation by distance.